Credence Signals in Beef Consumption: The Strategic Role of the “100% Autochthonous Breed” Label in Spain - Miguel A. Cantarero-Aparicio; José Manuel Perea; Alfonso Carbonero; Jennifer Claros-Zafra; Manuel Luque; Elena Angón (Foods)
This study evaluates the perceived value of the “100% Autochthonous Breed” label in beef purchasing decisions, comparing its influence with two well-established official certifications: organic and Protected Geographical Indication (PGI). A face-to-face survey was conducted with 900 consumers across Spain, using a choice-based conjoint experiment and hierarchical cluster analysis. The results indicate that although price is the primary determinant at the aggregate level, segmentation revealed distinct consumer profiles for whom the “100% Autochthonous Breed” label generated higher utility than other attributes. Specifically, four clusters were identified: Group I (18.6%) preferred the organic label; Group II (46.6%) prioritized low price; Group III (22.9%) valued the combination of PGI and the autochthonous breed label; and Group IV (11.9%) showed a preference for high-priced products featuring the “100% Autochthonous Breed” label. The findings highlight the strategic potential of this certification as a differentiation tool for sustainable, extensive, and territorially embedded livestock systems.